Los Varia Illustrium Virorum Poemata reunidos por Francisco López de Aguilar para alabanza de Lope de Vega y escarnio de Torres Rámila: Poemata I-XXV - García de Paso Carrasco, María Dolores; Rodríguez Herrera, Gregorio (1999)
This paper is the first part of a work that consists in the edition, annotated translation and literary commentary of the Varia illustrium virorum poemata, compiled by Francisco López de Aguilar to defend Lope de Vega and published in 1618. This first part includes just a brief introduction and the poemata I-XXV.
Keywords: Vega, Lope de, -- 1562-1635; Torres Rámila, Pedro de, -- 1583-1658; López de Aguilar, Francisco, -- 1585-1665; Filología clásica